2016
DOI: 10.1093/jrr/rrw075
|View full text |Cite
|
Sign up to set email alerts
|

The impact of epidermal growth factor receptor mutations on patterns of disease recurrence after chemoradiotherapy for locally advanced non–small cell lung cancer: a literature review and pooled analysis

Abstract: The purpose of this review was to evaluate the impact of epidermal growth factor receptor (EGFR) mutation status on disease recurrence in patients treated with chemoradiotherapy (CRT) for locally advanced non–small cell lung cancer (NSCLC). A literature search was conducted and a total of three studies were analyzed. There was no significant difference in the objective response rate between the EGFR mutation group and the EGFR wild-type group (odds ratios [OR] 1.46, 95% CI, 0.79–2.70, P = 0.228), and there was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 51 publications
2
11
0
Order By: Relevance
“…A phase III trial reported five‐year OS rates in stage III NSCLC patients treated with CCRT of 23% to 32% (for 74 Gy and 60 Gy, respectively) . Furthermore, longer survival was reported in a 2017 study of locally advanced NSCLC patients with m EGFR (vs. wild EGFR ) treated with CCRT, although the prognostic significance of m EGFR on recurrence was debated in a review paper published in 2016 . In the TKI group, our five‐year OS result was 26%, close to the 25% estimated in a recent systematic review (see Appendix B).…”
Section: Discussionsupporting
confidence: 74%
“…A phase III trial reported five‐year OS rates in stage III NSCLC patients treated with CCRT of 23% to 32% (for 74 Gy and 60 Gy, respectively) . Furthermore, longer survival was reported in a 2017 study of locally advanced NSCLC patients with m EGFR (vs. wild EGFR ) treated with CCRT, although the prognostic significance of m EGFR on recurrence was debated in a review paper published in 2016 . In the TKI group, our five‐year OS result was 26%, close to the 25% estimated in a recent systematic review (see Appendix B).…”
Section: Discussionsupporting
confidence: 74%
“…Our results were consistent with published meta-analyses that demonstrated that EGFR sensitizing mutations were not prognostic for localized NSCLC treated with definitive chemoradiotherapy or surgery [ 17 19 ]. Ochiai and colleagues performed a systematic review and meta-analysis of three retrospective non-randomized comparative studies to determine the impact of EGFR sensitizing mutations in locally advanced NSCLC treated with concurrent chemo-radiotherapy on patterns of recurrence, recurrence-free and overall survival [ 17 ]. They found that there was no difference in disease recurrence, recurrence free and overall survival between EGFR mutated and EGFR wild-type NSCLC, but there was a higher incidence of distant disease recurrence rate and lower incidence of locoregional recurrence rate for EGFR mutated NSCLC.…”
Section: Discussionsupporting
confidence: 92%
“…Other studies have also assessed the impact of EGFR mutations on treatment outcomes. 26,27 Ochiai et al 26 found no differences in the objective response rate (odds ratio 1.46, 95% CI 0.79-2.70) or the disease recurrence rate (odds ratio 1.37, 95% CI 0.68-2.75) after CRT between the EGFRm+ and EGFR wild-type groups. On the other hand, Tanaka et al 27 reported that PFS was significantly shorter in the EGFRm+ group and that the ratio of distant metastasis in patients with disease recurrence was relatively higher in this group than the EGFR wild-type group.…”
Section: Discussionmentioning
confidence: 98%